Current transition management of adolescents and young adults with allergy and asthma: a European survey. Issue 1 (7th October 2020) - Khaleva, Ekaterina; Vazquez‐Ortiz, Marta; Comberiati, Pasquale; DunnGalvin, Audrey; Pite, Helena; Blumchen, Katharina; Garriga‐Baraut, Teresa; Hox, Valerie; Santos, Alexandra F.; Gore, Claudia; Knibb, Rebecca C.; Alviani, Cherry; et al.
Abstract: Background: Transition from parent‐delivered to self‐management is a vulnerable time for adolescents and young adults (AYA) with allergy and asthma. There is currently no European guideline available for healthcare professionals (HCPs) on transition of these patients and local/national protocols are also mostly lacking. Methods: European HCPs working with AYA with allergy and asthma were invited to complete an online survey assessing challenges of working with these patients, current transition practices and access to specific healthcare resources. Results: A total of 1179 responses from 41 European countries were collected. Most HCPs (86%) reported a lack of a transition guideline and a lack of a transition process (20% paediatric HCPs, 50% of adult HCPs, 56% HCP seeing all ages). Nearly half (48%) acknowledged a lack of an established feedback system between paediatric and adult medical services. Many respondents never routinely asked about mental health issues such as self‐harm or depression and are not confident in asking about self‐harm (66.6%), sexuality (64%) and depression (43.6%). The majority of HCPs (76%) had not received specific training in the care of AYA although 87% agreed that transition was important for AYA with allergy and asthma. Conclusion: Although there was agreement that transition is important for AYA with allergy and asthma, there are crucial limitations and variations in the current provision of transition services across Europe. Standardisation of AYA management and specific training are required. This should improve management and continuity of care during adolescence and into adulthood to achieve the best healthcare outcomes. Abstract :